Comparison of Wright's Formula and the Dunn Method for Measuring the Umbilical Arterial Catheter Insertion Length - Se-ra Min; Hyeon-Soo Lee (Pediatrics and Neonatology)
Umbilical artery catheterization is the standard procedure for arterial access in neonatal intensive care units. An umbilical arterial catheter (UAC) needs to be placed accurately during the initial insertion because malpositioning increases catheter-related complications and subsequent repositioning exposes newborns to unnecessary handling, further radiologic exposure, and an increased risk of infection. To measure the UAC insertion length in newborns, we compared the conventional practice (i.e., the Dunn method) with a new formula: Wright's formula. Methods: The study enrolled 119 newborns. A nomogram derived from Dunn was used during the first study period and the new formula devised by Wright (4 × birth weight + 7 cm) was used during the second study period. The catheter tip position on the initial radiograph was evaluated as correct (i.e., T6–T10), overinsertion (i.e., <T6), or underinsertion (i.e., >T10). Results: The demographic profiles were not different between the two groups, which included sex; birth weight; and the number of preterm births, low-birth-weight (LBW) newborns, and very-low-birth-weight (VLBW) newborns. When using Wright's formula and the Dunn method, 83% of newborns and 61% of newborns, respectively, received a correct insertion (p < 0.05). The success rate for positioning the UAC tip between T7 and T8 was approximately two-fold higher when using Wright's formula than when using the Dunn method. In particular, the rate of correct insertion was significantly higher with Wright's formula in term newborns, LBW newborns, VLBW newborns, and small for gestational age (SGA) newborns (p < 0.05); however, the rate of overinsertion with the Dunn method was much higher in term newborns, LBW newborns, VLBW newborns, and SGA newborns (p < 0.05). Conclusion: The use of Wright's formula overall results in superior correct placement of the UAC tip. It may be a more accurate and practical method than the conventional practice for measuring the UAC insertion length in newborns.